Overview and Applications of Nanocarrier-Based Drug Delivery for Alleviating Alzheimer’s Disease - Sara Khan; Md. Faheem Haider; Nazish Naseem (Journal of Bio-X Research)
Alzheimer’s disease (AD) is a progressive neurodegenerative disorder characterized by cognitive decline and memory loss caused by the degeneration of neurons and the accumulation of amyloid plaques and tau tangles in the brain. The exact etiology of AD remains unclear, although both genetic and environmental factors play important roles. Key pathological features include synaptic dysfunction, oxidative stress, and neuroinflammation. Current treatments focus mainly on symptom relief through cholinesterase inhibitors and N-methyl-d-aspartate receptor antagonists. However, there is an ongoing effort to discover disease-modifying therapies. Recent clinical trials are investigating innovative approaches such as amyloid-targeting agents, tau aggregation inhibitors, and gene therapies. This paper offers a thorough overview of AD, presenting its fundamental aspects, contributing factors, primary disease mechanisms, current therapeutic strategies, and a detailed examination of ongoing clinical trials. In the context of advancing research, this paper provides valuable insights into the multifaceted approaches being explored to improve the understanding and management of this challenging neurodegenerative disorder.